A DISCUSSION ON THE ISSUE OF COSTS IN RELATION TO DERIVATIVE PROCEEDINGS IN SECTION 165 OF THE COMPANIES ACT 71 OF 2008 - Darren Subramanien (Obiter, 2021)
A historical practical obstacle to the institution of derivative proceedings has been the burden of costs. The burden of costs was identified as problematic as long ago as 1970 in the Van Wyk De Vries Commission of Inquiry into Companies and has the potential to continue to disincentivise derivative proceedings in light of the provisions of section 165 of the Companies Act 71 of 2008. Comparable provisions in the United Kingdom Companies Act 2006 are discussed to identify whether any improvements can be made with respect to the issue of costs in instituting derivative proceedings under section 165.